Exploring Digital Discourtesy: Impoliteness Strategies In K-Drama Fan Discourse on Social Media - Pratama, Agus Darma Yoga; Suastha, Putu Vania Maharani (ppjbsip, 2024)
This study analyzes impoliteness strategies used by netizens in responses to the variety show